1974
DOI: 10.1098/rstb.1974.0016
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelopes: Structure and biochemistry of the nuclear envelope

Abstract: The ultrastructure of the nuclear evelope is described in various cell types with special emphasis on its pore complexes (p.c.). The architecture of the p.c. is defined against the properties of other membranous pore formations. Evidence is presented that the non-membranous p.c. components contain ribonucleoproteins but do not represent the attachment sites of nuclear chromatin. The possible dynamic nature of the p.c. material is discussed in relation to nucleocytoplasmic translocation processes. DNA of the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 93 publications
(141 reference statements)
7
100
0
Order By: Relevance
“…vesicles, without fusion, occurred in the presence of the nonhydrolyzable ATP analogue, ATP-v-S. Wilson and Newport (1988) have also shown that ER vesicles alone are not sufficient for NE assembly in egg extracts. On the other hand, the'NE membrane shares biochemical markers with the ER and is often continuous with it (Franke, 1974). Since lamin B also remains associated with the ER during mitosis in chick tissue culture cells (Stick et al, 1988), one would expect NE membrane proteins to copurify with ER proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vesicles, without fusion, occurred in the presence of the nonhydrolyzable ATP analogue, ATP-v-S. Wilson and Newport (1988) have also shown that ER vesicles alone are not sufficient for NE assembly in egg extracts. On the other hand, the'NE membrane shares biochemical markers with the ER and is often continuous with it (Franke, 1974). Since lamin B also remains associated with the ER during mitosis in chick tissue culture cells (Stick et al, 1988), one would expect NE membrane proteins to copurify with ER proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In interphase, nuclear constituents are separated from the rest of the cell by the nuclear envelope (NE), t which consists of two membranes: an outer membrane which is continuous with the ER (Franke, 1974;Franke et ai., 1981), and an inner membrane which abuts the nuclear lamina that lies below it (Aebi et al, 1988). The nuclear lamina binds to chromatin, probably anchoring the interphase chromosomes to the NE (for review see Newport and Forbes, 1987;Gerace and Burke, 1988).…”
mentioning
confidence: 99%
“…In fact, there is good evidence to indicate that certain defined features of the chromosomecentromeres, telomeres and constitutive heterochromatin-interact with the nuclear envelope in a very specific way (Comings, 1980). In particular, the centromeres and telomeres are thought to be attached to the nuclear envelope at fixed locations which are only disrupted during cell division (Franke, 1974). Even then, it has been shown that pieces of the nuclear envelope remain attached to the chromosomes (Stubblefield and Wray, 1971).…”
Section: Discussion (A) Karyotypic Variation Within the Hybrid Zonementioning
confidence: 99%
“…The nuclear volume drops slightly over a more than twofold increase in DNA content of flat (11) diploid cells in culture. The volume for spherical (O) nuclei of mammalian origin becomes larger with an increase in DNA content due to heteroploidy.…”
Section: Figure 14mentioning
confidence: 99%